Estimation of seasonal methane fluxes over a Mediterranean rice paddy area using the Radon Tracer Method (RTM) - R. Curcoll; A. Àgueda; J.-A. Morguí; L. Cañas; S. Borràs; A. Vargas; C. Grossi; C. Grossi (Atmospheric Chemistry and Physics)
The Ebro River Delta, in the northwestern Mediterranean basin, has an extension of 320 km2 and is mainly covered by rice fields. In the framework of the ClimaDat project, the greenhouse gases atmospheric station DEC was designed and installed in this area in 2013. The DEC station was equipped, among other tools, with a Picarro G2301 instrument and an ARMON (Atmospheric Radon Monitor) to measure both CH4 and CO2 and 222Rn concentrations, respectively.